The Analysis of Strength of Cement Fiber Pipes with The Utilization of Economic Mixed Fiber as a Mixed Material - Heri Sujatmiko (Lowland Technology International, 2021)
Water is one of the main factors in human life. This fact brings us to the problem that often occurs, namely the use of low-quality water for the purpose of washing, bathing, cooking and drinking. The characteristics of such water in general, among others, the water is cloudy or dull, sometimes somewhat smelling rust and rancid, if exposed to sunlight for a long time, changes color to brownish black. In addition to feeling less comfortable, if this water is used to wash it will give a yellow stain on the clothes. A healthy way is to use a pipe or closed channel. Commonly used water lines are using bamboo pipes, which are rather expensive are PVC pipes and iron pipes. Especially if you use a large pipe size and for long distances, the required costs will be expensive. For rural areas, of course the problem of the availability of costs also needs attention. By paying attention to the things mentioned above, we will develop a method of making pipes that are simple, using materials that are easily available, and more importantly can be made alone, namely pipes with a mixture of palm fiber and cement. With the use of cement fibers, it is intended to apply the operational process to water with good quality.